Articulating occupational justice in healthcare for Filipino lesbians, gays, bisexuals, and transgender individuals - Delos Reyes, Rod Charlie; Erlyn A. Sana, PhD (2025)
This dissertation explored the current landscape of Filipino lesbians, gays, bisexuals, and transgender (LGBT) individuals in healthcare. Accessing healthcare, a fundamental occupational and human right, is often compromised for the LGBTs due to systemic biases and knowledge gaps among healthcare professionals. This study aimed to critically illustrate Filipino healthcare services for the LGBT community from an occupational justice perspective. Occupational justice refers to the equal opportunity for participation by all people in everyday activities. Using a convergent parallel mixed-methods design, the study incorporated quantitative data from the Knowledge, Attitudes, and Practices Towards LGBT in Healthcare Questionnaire (KAP-LHQ) and qualitative insights from a photovoice project. Descriptive statistics were used to analyze quantitative data, and thematic analysis was used for qualitative data. The rigor and trustworthiness of both analyses were assured through member checking, audit trail, and triangulation. The KAP-LHQ survey of 132 Filipino health professionals disclosed significant knowledge gaps, where more than 70% of respondents had not been aware of the basic terminology related to LGBT people, and 58% reported never having any direct experience with LGBT clients despite previous training in gender sensitivity. These findings, along with accompanying visual images, were generated from a photovoice project conducted with eight LGBT individuals and have proved to clearly illustrate occupational deprivation, alienation, and systemic barriers to healthcare access. Key findings showed that unawareness among health professionals upholds occupational injustices, and negative experiences in healthcare define occupational deprivation and alienation for LGBT people. However, positive attitudes and inclusive practices among healthcare professionals can enable occupational justice and promote health equity. The study underscores the necessity of culturally competent education, gender-affirming policies, and systemic reforms to address these gaps. This dissertation contributes to the discourse on occupational justice by highlighting healthcare as a critical site for addressing inequities faced by marginalized communities. By advocating for targeted training and inclusive practices, the study provides a possible foundation for advancing dignity, inclusiveness, and equity in Philippine healthcare systems, ultimately fostering meaningful healthcare occupations for the LGBT community.
Thesis (PhD)
print & pdf
Keywords: LGBTQ; Gender studies; Occupational justice; Healthcare